A new species of Cypriconcha Sars (Crustacea: Ostracoda) from high mountainwetlands of Argentina - Díaz, Analía R.; Lopretto, Estela C. (Zootaxa, 2009)
Cypriconcha hypsophila n. sp. is described and illustrated from high-altitude freshwater bodies within the Argentine province of Catamarca, which represents the first record of this genus in South America. This paper also presents a taxonomical key for identification of all species within the genus. Some comments concerning how this particular species could have spread from the high mountains from the Nearctic region to those of the northwestern Andes are provided.